1999
DOI: 10.1002/(sici)1097-4628(19990822)73:8<1457::aid-app15>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Miscibilization of low molecular weight functionalized polyethylenes in epoxy resins. I. Effects of composition and modifications chemistry

Abstract: ABSTRACT:Toughening of epoxy resins is traditionally carried out by adding small proportions of a low T g oligomer containing reactive end groups. These induce the precipitation of crosslinked rubbery particles during curing. In this study, an investigation was carried out to examine the possibility of using randomly functionalized low molecular weight polyethylene for the same purpose. In the first part of the work we examined the miscibility of binary and ternary blends of several low molecular weight polyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the tensile tests on PCL samples, once necking starts to appear in the mid cross-section, it propagates along the entire length of the dumbbell specimens, reaching elevated strain values. The material starts yielding around [16][17] MPa and once the necking begins, there is a drop in the stress to about 12 MPa. Then, the plastic deformation propagates maintaining a constant stress, up to a strain of 250%.…”
Section: Characterization Of the Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tensile tests on PCL samples, once necking starts to appear in the mid cross-section, it propagates along the entire length of the dumbbell specimens, reaching elevated strain values. The material starts yielding around [16][17] MPa and once the necking begins, there is a drop in the stress to about 12 MPa. Then, the plastic deformation propagates maintaining a constant stress, up to a strain of 250%.…”
Section: Characterization Of the Constituentsmentioning
confidence: 99%
“…The high mechanical, thermal, and chemical properties achievable in epoxy/thermoplastic blends make them suitable for different applications, such as matrices for composites, materials with self-healing and shape memory characteristics, and aerospace components with good strength and fracture toughness [11]. In the literature, it can be found that several thermoplastic polymers were used for blending epoxy resin, such as polycarbonate (PC), poly(caprolactone) (PCL), and poly(ethylene terephthalate) (PET), and different kinds of polyolefins [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In the processing of these blends, the epoxy base, the curing agents and thermoplastic pellets or powders are usually mixed together.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the trifunctional epoxy resin triglycidyl p ‐aminophenol (TGAP) has received considerable attention; however, its high cross‐link density, and hence, high glass transition temperature, leads to materials that are inherently brittle. To increase their toughness, thermoplastic (TP) modifiers, rubber particles, hyperbranched polymers, or reduced carbon nanotubes, have been incorporated to these thermosetting systems. A typical characteristic of epoxy/TP blends is reaction induced phase separation that occurs upon curing.…”
Section: Introductionmentioning
confidence: 99%
“…Cured thermosetting resins are intrinsically brittle as consequence of their high crosslinking density. For this reason, they are traditionally toughened by dissolving a small proportion (10–20%) of a liquid rubber containing reactive end groups in the liquid epoxy system and inducing the precipitation of crosslinked rubbery particles during curing 4. The resulting toughened systems possess an increased viscosity and require elevated values of temperature and pressure to be injected.…”
Section: Introductionmentioning
confidence: 99%